Convenient syntheses of fullerynes for 'clicking' into fullerene polymers. Issue 1 (1st January 2017) - Teng, Fu-Ai; Guo, Yanli; He, Jianping; Zhang, Yong; Han, Zhewen; Li, Hui
Abstract: Alkyne-functionalized fullerenes (fullerynes) were designed and conveniently synthesized via Bingel reaction in one step with high yields. They were used to react with azido-functionalized polystyrene (PS) via Huisgen [3 + 2] cycloaddition 'click' chemistry to form two fullerene polymers: one with C60 tethered to the end of a PS chain (C60 -1PS) and the other with C60 tethered at the junction point of two PS chains of identical molecular weight (C60 -2PS). The fullerene polymers were characterized by 1 H NMR, 13 C NMR, FT-IR, MALDI-TOF mass spectrometry and SEC. The results showed that the fullerene polymers are well-defined with narrow polydispersity and high fullerene functionality. Besides, aggregation of C60 in THF was observed in the SEC traces. The optical properties of the fullerene polymers were studied by UV–Vis absorption spectroscopy, and the results suggested that the PS chain(s) on the fullerene core has no remarkable effect on the optic property of C60 . The thermal properties of the fullerene polymers were studied by TGA and DSC, and the results indicated that the two fullerene polymers with different C60 content and distinct molecular topology may have different self-assemble architectures in the solid state. The well-defined fullerene polymers can be used as model compounds to study the self-assemble architecture of shape amphiphiles based on polymer-tethered molecular nanoparticles.